Consistent Expectations Equilibria and Complex Dynamics in Renewable Resource Markets - Cars H. Hommes; J. Barkley Rosser (Tinbergen Institute, 2001)
Price fluctuations under adaptive learning in renewable resourcemarkets such as fisheries are examined. Optimal fisherymanagement with logistic fish pOpUlation growth implies a backward-bending, discounted supply curve for bioeconomicequilibrium sustained yield. Higher discount rates bend supplybackwards more to generate multiple steady state rationalexpectations equilibria. Under bounded rationality adaptive learningof a linear forecasting rule generates steady state, 2-cycle as weIl as chaotic consistent expectations equilibria (CEE),which are self-fulfilling in sample average andautocorrelations. The possibility of learning to believe in chaosis robust and even enhanced by dynamic noise.
Keywords: 330; Erneuerbare Ressourcen; Adaptive Erwartung; Beschränkte Rationalität; Chaostheorie; Cobweb; Lernprozess; Prognoseverfahren; Theorie